Comparative analysis of the use of Community Health Workers while deploying the Attractive Targeted Sugar Bait (ATSB) for malaria control in Western Province, Zambia - Frank Ndalama; David Mulenga; Annie Arnzen; Situmbeko Akalalambili; Titus Tobolo; Chuma Maluma; Chama Chishya; Kochelani Saili; Ruth A. Ashton; John Miller; Kafula Silumbe; Javan Chanda; et al. (Malaria Journal)
Abstract Background Community Health Workers (CHWs) play a crucial role in malaria control efforts, yet their contributions to large-scale field trials remain understudied. This research examined the management of CHWs recruited to support a phase III trial of Attractive Targeted Sugar Baits (ATSBs) in Western Zambia. The study aimed to understand the extent to which CHW involvement in the trial aligned with best practices and challenges faced by CHWs implementing health promotion activities. Methods A literature review, review of Zambia Ministry of Health Guidelines, and review of WHO guidelines was conducted to identify best practices and common challenges for CHWs contributing to the delivery of malaria interventions. Subsequently ATSB trial documents were reviewed to compare CHW involvement and CHW challenges experienced during the ATSB trial from 2021 to 2023. A comparative analysis was utilized to assess the involvement of CHWs in the ATSB trial against literature review findings, specific to CHW recruitment, training, supervision, incentivization, and community support. Results Five best practices for CHW delivery of interventions were identified: participatory and gender equitable recruitment and selection; comprehensive training; incentivization for enhanced motivation and performance; high quality supportive supervision; and fostering community support. Five common challenges for involving CHWs in programme delivery were identified: inadequate and poor-quality supervision of CHWs; low compensation and motivation; logistical constraints; workload and multiplicity of roles, and community challenges. The analysis found that ATSB trial practices largely aligned with literature best practices and established guidelines, particularly in training and incentive structures. However, challenges were identified in achieving gender balance (32% female CHWs in year 2), community involvement in CHW selection, and coordination between CHWs and research team members. CHW involvement was a key factor towards successfully implementing the trial protocol. Conclusions Experiences with CHWs involvement in the ATSB trial in Zambia suggest that some facets of field research readily facilitate adherence to best practices for CHW recruitment and management. Additionally, field research that is adequately funded and characterized by rigorous implementation may avoid some of the common challenges faced by CHWs implementing health promotion activities. Nonetheless, some CHW cadre challenges appear universal to programmatic and research contexts, including an imbalance in gender representation favouring male participation in CHW opportunities. More documentation of research experiences may be needed to understand CHW involvement and experiences in field research outside of randomized controlled trials.